Comparison of tape stripping with the human skin blanching assay for the bioequivalence assessment of topical clobetasol propionate formulations. - Wai Ling Au; Michael F Skinner; Isadore Kanfer (Frontiers Media S.A., 2010)
Purpose: A draft guidance on tape stripping for assessing the bioavailability/bioequivalence of topical formulations was issued by the United States Food and Drug Administration in 1998 but has since been withdrawn. This was due to problems associated with the method and also inconsistencies and variability in the resulting data. The purpose of this study was to re-visit the tape stripping technique, incorporate refinements to reduce variability and validate the method using bioequivalence data obtained from the assessment of a topical corticosteroid cream containing 0.05% clobetasol propionate using the human skin-blanching assay. Methods: A pilot tape stripping study was conducted to establish the variability of the formulations.The bioequivalence of two different commercially available clobetasol propionate cream formulations and a clobetasol propionate ointment formulation were subsequently investigated using the tape stripping method. Results: The data from the pilot tape stripping study correlated well with data from the human skin-blanching assay. A subsequent pivotal tape stripping study confirmed bioequivalence between the two cream formulations whereas bio-inequivalence was demonstrated between the cream and ointment formulations.Conclusions: These studies show that the results from tape stripping concur with data from the human skin blanching assay and demonstrate the potential of a well-controlled tape stripping study as an option for the assessment of bioequivalence of topical corticosteroid formulations.